Nonlinear numerical analysis of non-planar rectangular hollow structural section connections - Knox, Nathan (Kansas State University, 2022)
This thesis summarizes a study performed to evaluate the ability of General Purpose and Component Based Finite Element solvers to accurately predict the strength and deformation characteristics of non-planar Rectangular Hollow Structural Section joints (RHSS). There are no known empirical equations for non-planar connections. Therefore, these connections can only be designed by means of advanced analysis or by using empirical equations developed based on experimental tests of planar connections. The geometry of non-planar connections tends to result in the branch connecting at the corner of a chord, resulting in a stiffer connection. Therefore, it is reasonable to hypothesize that non-planar connections may have increased capacity compared to standard planar connections, at least when considering the chord wall plastification failure mode. A Research Oriented Finite Element program (Abaqus) and Design Oriented Finite Element program (Idea StatiCa) were used in this study. A verification and validation procedure was used in this study to (1) verify the mathematical models were properly calibrated and had an acceptable level of error and (2) validate that the mathematical models adequately predict the physical behavior of the real connection. Experimental data used to validate the numerical models was gathered from a combination of previously published papers and original experiments performed at the Kansas State University Civil Engineering Laboratory. The scope of the experimental program performed for this thesis was too limited to provide a definitive answer to the research question; however, the results are favorable and suggest that each finite element strategy can be used to accurately analyze and design complex RHSS joints. The planar numerical models created in Abaqus predicted the relevant System Response Quantities (SRQs), local deformation and plastic strain, within 5% when compared to available experimental data, IDEA StatiCa consistently under-predicted the capacity of these connections. When comparing Abaqus numerical results of bird beak connections to AISC empirical equations for a planar analogue connection the bird beak connection was shown to have significantly more chord wall plastification capacity for the connections studied. Bird beak connections had > 9% more capacity than their planar analogue in all cases. More research in this area is needed to evaluate if non-planar connections have more capacity than planar connections when considering a more complete range of connection dimensions, branch angles, and loading types.
Keywords: hss; FEA; Finite element analysis; Steel; Connection